MPC-based control strategy of PV grid connected inverter for damping power oscillations - Wen, Xichang; Wu, Ting; Jiang, Hui; Peng, Jianchun; Wang, Huaizhi (Frontiers in Energy Research, 2022)
With global warming and the depletion of fossil energy, the development of photovoltaic (PV) energy has attracted attention in many countries. However, when large-scale PV power stations are connected to the power grid through inverters, the inertia and damping capacity of the power system are greatly reduced, leading to frequent power oscillations in the power system. To solve this problem, this study proposes a control strategy for PV grid-connected inverters based on the model predictive control (MPC) algorithm. Based on the MPC algorithm and the establishment of a discrete-time predictive model, the PV grid-connected inverter dynamically adjusts its output current to suppress power oscillations. The simulation results demonstrated the effectiveness of the proposed control strategy in damping power oscillations in the power grid and enhancing the stability of the power system.